The Relevance of The Application of Innovative Technologies in Medical Education (Journal of Pedagogical Inventions and Practices, 2023)
This article explores the growing relevance of applying innovative technologies in medical education. It discusses the methods, results, and implications of integrating digital tools, simulations, and virtual reality into medical training. The paper concludes with suggestions for the continued adoption of technology in medical education to better prepare future healthcare professionals